2022
DOI: 10.1002/ece3.9395
|View full text |Cite
|
Sign up to set email alerts
|

Salinity‐induced transcriptome profiles in marine and freshwater threespine stickleback after an abrupt 6‐hour exposure

Abstract: Saltwater and freshwater environments have opposing physiological challenges, yet, there are fish species that are able to enter both habitats during short time spans, and as individuals they must therefore adjust quickly to osmoregulatory contrasts. In this study, we conducted an experiment to test for plastic responses to abrupt salinity changes in two populations of threespine stickleback, Gasterosteus aculeatus, representing two ecotypes (freshwater and ancestral saltwater). We exposed both ecotypes to abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 103 publications
1
2
0
Order By: Relevance
“…Previous reports have indicated adverse effects of hypotonic stress on various developmental stages of Macrobrachium rosenbergii larvae; the expression of the autophagy-related gene atg7 showed significant changes under hypotonic stress [76]. In salinity-induced transcriptome studies of marine and freshwater threespine stickleback, a decrease in usp45 expression was observed 6 h after the sudden exposure to seawater [77]. Notably, our genomic analyses found that there were CNEs loss near the atg7 and obtain close to usp45 (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Previous reports have indicated adverse effects of hypotonic stress on various developmental stages of Macrobrachium rosenbergii larvae; the expression of the autophagy-related gene atg7 showed significant changes under hypotonic stress [76]. In salinity-induced transcriptome studies of marine and freshwater threespine stickleback, a decrease in usp45 expression was observed 6 h after the sudden exposure to seawater [77]. Notably, our genomic analyses found that there were CNEs loss near the atg7 and obtain close to usp45 (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, alcohol metabolism was also enhanced in the gills. For most saltwater fish, a decrease in water salinity alters their oxygen requirements in gills, thus may increase the production of lactate (Ern et al, 2014; Taugbøl et al, 2022). To combat the adverse impact of lactate buildup, crucian carp and goldfish ( Carassius , Cyprinidae) can further covert lactic acid to ethanol and excrete it into ambient water via the special coupling of pyruvate dehydrogenase complex (PDC) and alcohol dehydrogenase (ADH) in gills, which largely improve their tolerance to low oxygen environment (Fagernes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chloride channels play a key role in the osmoregulatory physiology of all animals, with CLCN2 differentially expressed in euryhaline fish exposed to osmotic stress (Bonzi et al, 2021; Su et al, 2020b). Another member of the anoctamin family, ANO1 , related to osmoregulation, was differentially expressed in fish under osmotic stress (Taugbøl et al, 2022). KCNN3 is a potassium-activated channel that has been proven to be differentially expressed in euryhaline fish exposed to osmotic stress (Bonzi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%